The Case for an Anchored cause - Hill, Angelica (Proceedings of the Amsterdam Colloquium, 2024)
In this paper I propose the meta-predicate cause can be reduced to a circumstantial modal assuming an anchor semantics. To show this I focus on the semantics of strong overt causative expressions, in English, e.g., made, forced, got, and propose they are circumstantial modals with a syntactically explicit modal anchor. This proposal endorses a semantics in which modal components are independently provided by syntax, straightforwardly predicts the distinction between strong and weak overt causatives, eliminates vagueness from our semantic terminology, and accounts for the close relation between linguistic expressions that have received independent treatments in the literature.